The Effectiveness of Padlet as an Instructional Media to Improve Students' Performance in Writing Descriptive Text - Sri Wahyuni (Universitas Negeri Surabaya, 2023)
Writing is a difficult skill in learning English. To assist students in improving their performance in writing skills, teachers must be creative and innovative. In 21st-century learning, involving technology can support the learning process. One type of technology that can assist the learning process is Padlet. This study focuses on the effectiveness of Padlet as an instructional media to assist students in improving their abilities when writing descriptive texts. This study aims to determine the effectiveness of using Padlet as an instructional media to improve student performance in writing descriptive texts. This research was conducted in one of the junior high schools in Surabaya. The researcher chose 60 students from grade 7 as the subject of this research. This research is an experimental quantitative research. There are two classes to be studied: class 7H as the control class and class 7G as the experimental class, each class consists of 30 students. The experimental group will be taught using Padlet media, while the control group will be taught using conventional media. This study uses research measuring instruments in the form of pre-test and post-test. The data from this study will be analyzed using SPSS with the Independent Sample T-Test formula. The results showed that Padlet effectively improved students' performance in writing descriptive text. Keywords: Instructional Media, Padlet, Descriptive Text